The factors that influencing employee’s performance: a study among government servants at Department of Statistics Malaysia, Kelantan / Mohd Afiq Mohd Zamri - Mohd Zamri, Mohd Afiq (Bachelor of Science (Hons.) Statistics, 2015)
In the world of work, there are many factors needed by every employee in order to perform well in the organization. The organization will develop and successful if every employee works at their high level performance and also more efficient and productive. This study was done to investigate the factors that influencing employee’s performance that involve all government servants at Department of Statistics Malaysia (DOSM), Kelantan. The factors that involved in the study were personality, skill, experience, motivation and working environment. The primary data was used in the study and data was collected which a set of questionnaire was distributed among 135 of 206 government servants at DOSM through personal interview. Stratified sampling method was used in this study and respondent from each stratum was chosen randomly by using Microsoft Excel. The proportional allocation sample size formula was used to determine the total sample size for each stratum. The data collected were analyzed by using logistic regression through Statistical Package for Social Science (SPSS) version 20